The Participation of Fisherman Groups in Community Empowerment Activities (A Study of Community-Based Coral Reef Rehabilitation in Baurung, Banggae Timur, Majene) - Qadir, Muhammad Muhtaj; Gunawan, Budhi; Iskandar, Iskandar (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2021)
This study aims to describe (1) the comprehensive implementation of coral reef rehabilitation activities which have been carried out in Baurung Village, Banggae Timur District, Majene Regency, Sulawesi Barat, and (2) the participation of fisherman groups who have been directly involved in the coral reef rehabilitation activities. This study employs qualitative methods which data are collected through observation and interviews. The research participants were selected through purposive sampling and involved activity executor and the Head of the Fisherman Group from Samaelo dan Sipatuo. The results demonstrated that (1) The implementation of coral reef rehabilitation activities was carried out in four stages, namely preparation, implementation, monitoring/evaluation and maintenance, (2) The participation of fisherman groups shows that in the preparation and implementation stages, their participation is considered high, while their participation in monitoring/evaluation and maintenance stages tends to decrease. Therefore, it brings an impact to the activity results.